BUILDING ENVIRONMENTAL AWARENESS AMONG PRESCHOOLERS - Пристайко, Мария; Джура, Наталья (SWorldJournal, 2020)
The formation of ideas about the environment and human impact on its condition is the main task of environmental education. The article considers the importance of preschool environmental education and the main aspects of building environmental awareness